A plug'n'play WiFi surface-mount dual-loop antenna. (April 2017) - Chamorro-Posada, Pedro; Vázquez-Cabo, José; Rodríguez, José L.; López-Santos, José M.
Abstract: We present the design, modelling and characterization in the 2.4 GHz band of a B-shaped antenna consisting of a dual circular loop over a conductor plane. The proposed design is intrinsically unbalanced and features a very good match to a 50 Ω line at resonance, which makes our device essentially plug'n'play for a coaxial cable feed. Another interesting property of the proposed antenna is its simplicity of construction. The antenna has been modelled using the moment method. A prototype resonant at 2.4 GHz has been built and we have measured its impedance in this spectral region. The radiation pattern and the gain at resonance have also been characterized and the device has been shown to provide 6.31 dBi gain. The overall properties of the device make it an excellent option to provide WiFi connectivity when required in open hardware implementations.